The payment and insurance of ransom: an analysis of legality, morality and possible solutions in the case of ship hijackings by pirates - Hermanussen, Christian (Shipping Law Unit, 2026)
Piracy has been perceived as a menace of times long gone and has until recently been associated with romantic tales of one-legged and free-spirited men, roving the Caribbean Sea for bounty and gold. In recent years, however, a new type of pirate has emerged in one of the most lawless spots in the world. The pirates of Somalia increasingly threaten one of the busiest commercial shipping routes, thus forcing shipowners to pay higher insurance premiums or to reroute around the Cape. Either way, the current situation tremendously increases the costs of shipping in the Indian Ocean and threatens life of seamen. The purpose of Somali pirates is to obtain high ransom sums. Their demands are frequently met by intimidated shipowners who then turn to their insurers for cover. This practise has led to enormous profits for both the insurers as well as the pirates. Until today, no solution has been found to break the vicious circle in which shipowners find themselves.